2011
DOI: 10.1074/mcp.m111.010090
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Isolation and Glycosylation Analysis of IgG–Variability and Heritability of the IgG Glycome in Three Isolated Human Populations

Abstract: All immunoglobulin G molecules carry N-glycans, which modulate their biological activity. Changes in N-glycosylation of IgG associate with various diseases and affect the activity of therapeutic antibodies and intravenous immunoglobulins. We have developed a novel 96-well protein G monolithic plate and used it to rapidly isolate IgG from plasma of 2298 individuals from three isolated human populations. N-glycans were released by PNGase F, labeled with 2-aminobenzamide and analyzed by hydrophilic interaction ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
333
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 446 publications
(349 citation statements)
references
References 75 publications
14
333
1
1
Order By: Relevance
“…The assignment of glycan structures by HILIC-UPLC in serum was performed by comparison with an updated GlycoBase 3.2 (http://glycobase.nibrt.ie/), as well as published assignments. 13,32 Assignment of the IgG glycans in each peak was based on the analysis in Pucic et al 34 Glycan feature statistical analysis…”
Section: Oxford Glycan Annotation Systemmentioning
confidence: 99%
“…The assignment of glycan structures by HILIC-UPLC in serum was performed by comparison with an updated GlycoBase 3.2 (http://glycobase.nibrt.ie/), as well as published assignments. 13,32 Assignment of the IgG glycans in each peak was based on the analysis in Pucic et al 34 Glycan feature statistical analysis…”
Section: Oxford Glycan Annotation Systemmentioning
confidence: 99%
“…Galactosylation of IgG is one of the most comprehensively studied glycosylation features, and galactose ratios (G-ratios) have been identified as highly informative indicators of the level of galactose incorporation (8). We determined peak % areas of agalactosylated (G0), mono-(G1) and digalactosylated (G2) structures to provide a quantitative measurement of galactose incorporation into released undigested IgG N-glycans.…”
Section: Soluble Leptin Receptor (Sob-r)mentioning
confidence: 99%
“…Glycosylation is a widespread post-translational modification of proteins and deregulation of glycosylation is associated with a wide range of diseases (8). Along these lines, we have previously described galactose incorporation ratios as a method of studying the presence of N-glycan processing defects in children with galactosemia (7).…”
mentioning
confidence: 99%
“…13-15 It is now widely recognized that removal of the core fucose from Fc N -glycans represents the most effective approach to enhance ADCC activity 14 15 A high-throughput study of the IgG glycome of three isolated human populations showed that most of the human plasma IgG antibodies are core fucosylated with levels of afucosylated IgG ranging from 1.3% to 19.3%, underlying the difference in ADCC efficacy of naturally occurring antibodies to protect against diseases 16 . Dramatic shifts in IgG glycan profile towards reduced galactosylation and fucosylation have been observed in human immunodeficiency virus (HIV)-specific antibodies and are associated with improved antiviral activity and HIV control 17 …”
Section: Introductionmentioning
confidence: 99%